Municipal administration in Srinagar (J&K) - A review - Nahvi, G.L. (2003)
Municipal corporations across the country are faced with burden of increasing urbanisation on one hand and the financial constraints on the other. The heavy demand on civic services, expanding city limits and an unmindful dependence on the administration have rendered most of the municipal corporations ineffective in their entrusted task. This article deals with the municipal administration of the city of Srinagar which had a history going back to the second half of the 19th Century. The new J&K Municipal Corporation Act, that come into force very recently, holds much promise for the citizens of this beautiful city. - Reproduced.
Keywords: Local government - India - Jammu and Kashmir; Local government